Pensamiento automático y su influencia en el estrés postraumático de una estudiante universitaria de 28 años de edad - Engracia Bravo, Bilexi Menali (2020)
In the development of this case: Automatic thinking and its influence on post-traumatic stress in a 28-year-old university student, the objective was carried out: to know if automatic thoughts influence a diagnosis of post-traumatic stress in an adult woman, applying the clinical interview and the exploration of the mental state. Psychological tests were used; Beck's depression inventory, Hamilton's anxiety scale and Davidson's trauma scale, which contributed to know the signs and symptoms of his emotional, behavioral and thought alteration, obtaining as a diagnosis the post-traumatic stress disorder found in the ICD 10 and DSM 5, to finally give treatment through cognitive behavioral therapy.